Розробка інформаційної системи для мережі кінотеатрів - Шалаєв, Є. Р. (ХНУРЕ, 2024)
The rapid development of technology has transformed the entertainment industry, including the movie-going experience. Nowadays, moviegoers expect a convenient and personalized experience when booking tickets and interacting with cinemas. To meet these expectations, cinema chains are increasingly turning to web applications as a way to enhance customer engagement and streamline operations. The developed system will help the moviegoers with booking the tickets for their favorite movie from home, which will make the whole process much more comfortable and easier.
Keywords: кінотеатрська система; управління сеансами; бронювання квитків; інформаційна платформа; облік показів